2023
DOI: 10.1111/jvim.16845
|View full text |Cite
|
Sign up to set email alerts
|

Localization and characterization of atrial depolarization waves on the surface electrocardiogram in dogs with rapid supraventricular tachycardia

Stefano Battaia,
Manuela Perego,
Damiano Cavallini
et al.

Abstract: BackgroundSupraventricular tachycardias (SVTs), despite having various anatomical substrates and pathophysiological mechanisms, frequently show similar electrocardiographic presentations.ObjectivesTo locate and characterize atrial deflections (ADs) on 12‐lead electrocardiograms in dogs with sustained rapid SVT and assess the utility of different electrocardiographic variables in differentiating types of tachycardia.AnimalsNinety‐two dogs with orthodromic atrioventricular reciprocating tachycardia, 17 with atri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…2), both QRS electrical alternans and TWA were observed simultaneously. QRS electrical alternans is common in human patients and dogs with OAVRT and is by most considered heart rate-dependent [4]. On the other hand, TWA could signal inhomogeneous tissue refractoriness [7] and may be related to an increased risk of sudden cardiac death in Doberman Pinschers [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), both QRS electrical alternans and TWA were observed simultaneously. QRS electrical alternans is common in human patients and dogs with OAVRT and is by most considered heart rate-dependent [4]. On the other hand, TWA could signal inhomogeneous tissue refractoriness [7] and may be related to an increased risk of sudden cardiac death in Doberman Pinschers [8].…”
Section: Discussionmentioning
confidence: 99%
“…Other than TWA, the above findings in dogs are most indicative of OAVRT and less so of atrial tachycardia and atrioventricular nodal re-entrant tachycardia [2][3][4]. Right atrial activation mapping during tachycardia revealed the earliest site of activation right postero-septal near the tricuspid annulus (Fig.…”
Section: Image Interpretationmentioning
confidence: 93%
“…[7][8][9] Also in veterinary practice, identifying the P waves is essential for differentiating between various types of supraventricular tachycardia, such as AFL, AT, orthodromic atrioventricular reciprocating tachycardia, and sinus tachycardia. 10 However, there has not been an equivalent method to the Lewis lead proposed in veterinary medicine, and the Lewis lead configuration described in humans cannot be directly translated to dogs due to differences in the anatomical and electrical axes of the heart across species. 11,12 Therefore, this study proposes new bipolar lead configurations to specifically evaluate atrial depolarization in dogs and investigate their characteristics by comparing them with conventional leads.…”
mentioning
confidence: 99%